The Corelation Of Students’ Mathematics Learning Engagement On Their Academic Performance In Junior High School - Zhang Li Jie; Zhou Ying; Mo Zong Zhao (Journal on Education, 2019)
In this study, 312 junior high school students are tested on their mathematics learning engagement and achievement. This research will also find out the connection between the students’ mathematics learning engagement with their mathematics academic performance. The results of this research show that junior high school students’ mathematics learning engagement is closely related to their mathematics academic performance in which cognitive engagement has the highest correlation and emotional engagement has the lowest correlation with students’ mathematics academic performance. The result also shows that when there is a higher mathematics academic achievement, the mathematics learning engagement will also be higher. This research also shows that gender factor doesn’t really affects the students’ mathematics learning engagement but their geographic factor does affect the learning engagement.